2018
DOI: 10.1002/art.40572
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Monosodium Urate Monohydrate Crystal Deposits Are Common in Asymptomatic Sons of Patients With Gout: The Sons of Gout Study

Abstract: ObjectiveTo estimate the prevalence and distribution of asymptomatic monosodium urate monohydrate (MSU) crystal deposition in sons of patients with gout.MethodsPatients with gout were mailed an explanatory letter with an enclosed postage‐paid study packet to mail to their son(s) age ≥20 years old. Sons interested in participating returned a reply form and underwent telephone screening. Subsequently, they attended a study visit at which blood and urine samples were obtained and musculoskeletal ultrasonography w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…In summary, our findings confirmed a heritability component for hyperuricemia and gout. This relationship was recently demonstrated in a cohort of asymptomatic male offspring of parents with gout, in which the male offspring had a significantly higher frequency of hyperuricemia, urate under-excretion, and prevalence of monosodium urate crystal deposits [24]. A positive family history is an important diagnostic clue; however, it may be absent in de novo mutations and where hyperuricemia/gout was either not diagnosed or not communicated to the rest of the family.…”
Section: Discussionmentioning
confidence: 94%
“…In summary, our findings confirmed a heritability component for hyperuricemia and gout. This relationship was recently demonstrated in a cohort of asymptomatic male offspring of parents with gout, in which the male offspring had a significantly higher frequency of hyperuricemia, urate under-excretion, and prevalence of monosodium urate crystal deposits [24]. A positive family history is an important diagnostic clue; however, it may be absent in de novo mutations and where hyperuricemia/gout was either not diagnosed or not communicated to the rest of the family.…”
Section: Discussionmentioning
confidence: 94%
“…Balancing sustained efficacy [7][8][9][10][11] with acceptable tolerability 1,12 A 2nd generation, JAK1 preferential inhibitor for moderate to severe RA [1][2][3][4][5][6] Refer to Summary of Product Characteristics (SmPC) before prescribing, and for full prescribing information.…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite side of the spectrum, some physicians believe that for a patient to develop tophi and severe symptomatic gout, it would usually be preceded by years of recurrent flares, since it has been well demonstrated that patients with asymptomatic hyperuricemia have MSU crystal deposits. [16][17][18][19] The 2020 American College of Rheumatology (ACR) recommendations support starting ULT if there are two or more flares in the previous year, evidence of tophi, or evidence of radiographic damage attributed to gout and conditionally recommend starting ULT for CKD stage 3, SU > 9mg/dL, or urolithiasis. 12 Will other societies support this?…”
Section: Timing Of Ult Initiation Is Controversialmentioning
confidence: 99%